"Please the women or die": silent cinema and the construction of female desire. Issue 1 (2nd January 2023) - Porter, Laraine
ABSTRACT: By the mid-1920s, the top echelons of the film industry on both sides of the Atlantic were almost entirely dominated by men. Despite women becoming the majority consumers for cinema culture, male studio bosses, producers, directors and publicists mediated women's tastes and expectations through the silent and early sound period. Taking Iris Barry's claim that cinema 'exists for the purpose of pleasing women' (Barry 1926, 59), this article considers how women became increasingly significant, not only as audiences for films but to the burgeoning consumer cultures surrounding cinema including magazines, novels, fashion, beauty and leisure. Additionally, Lisa Stead's assertion that 'The movies, and going to the movies, were for many British women an integral part of their experience of modernity' (2016, 1) is examined in relation to how women's tastes and patterns of consumption, helped steer the expansion of the cinema industry and its associated fan cultures. This article also addresses how young female cinemagoers and entertainment seekers were dismissed as 'flappers' and often excoriated by Britain's intellectual elite. It examines how cinema's stubbornly persistent male power base was forced to accommodate and address women's cultural tastes due to their numerical significance as consumers.